Uso de bioestimulantes a base de microalgas en planes de manejo orgánico de papa (Solanum tuberosum L.) - Le Roy-Cáceres, Alessandra (2025)
Potatoes are a strategic crop due to their productivity and nutritional value. In Costa Rica, they are primarily cultivated in Cartago, in the cantons of Oreamuno, Alvarado and Turrialba; and to a lesser extent, in Zarcero, Alajuela. However, conventional management practices have led to the excessive use of agrochemicals. In response, the application of biological biostimulants has emerged as a more sustainable alternative. The Microalgae Laboratory has developed a research and technology transfer line on this topic and, in collaboration with INA and INTA, initiated an outreach project that involved implementing biostimulants produced from microalgae in the organic management of potato crops. This project evaluated variables such as plant height and seed production within a potted system. The results indicated adequate assimilation of the biostimulant, showing a tendency to enhance production without negatively affecting plant development. Additionally, the project fostered stronger collaboration with organic farmers and facilitated the transfer of a management plan, which integrated microalgae-based biostimulants and organic potato seed produced from controlled experiments at TEC, to the participating farms, representing a significant step toward cleaner agricultural practices.